Is Greater Financial Independence Ahead for Universities? - Goodman, Roger (International Higher Education, 2009)
Universities face conflicting pressures of rising demand for their services, especially during recessions. One solution would be for universities and policymakers to simply manage within the existing constraints of the system by scaling back enrollments, delaying access for underserved populations, seeking out cost efficiencies, and limiting capital investment in the hopes of improved funding environments in the future. Another possibility is for the model of funding for higher education to evolve toward a public-market-based funding mix.